2016
DOI: 10.4172/2167-7956.1000139
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols Nanoencapsulation for Therapeutic Applications

Abstract: Natural polyphenols are valuable compounds present in plants, fruits, legumes, chocolate, tea, wine and marine organisms possessing scavenging properties towards radical oxygen species. These abilities make polyphenols interesting either for the treatment of various diseases like inflammation and cancer or for anti-ageing purposes in cosmetic formulations. Unfortunately, such compounds lack in long-term stability, are very sensitive to light, and often present a low water solubility and poor bioavailability. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 114 publications
(186 reference statements)
0
10
0
Order By: Relevance
“…In this context, the reduction of lipid peroxidation using lipophilic antioxidants derived from natural antioxidant molecules was a logical choice to reduce deleterious oxidative stress. Four natural phenolic derivatives were selected in this study for their potent antioxidant properties or for their previous evaluation in RPE cell assays: phloroglucinol [15], resveratrol [14], catechin, and quercetin [46,47]. Among them, natural quercetin has been largely evaluated in the field of retina dystrophies for its direct or indirect antioxidant properties: Cao et al [18] demonstrated the ability of quercetin to protect human RPE cells from oxidative stress in vitro via suppression of pro-inflammatory cytokines and inhibition of apoptosis pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the reduction of lipid peroxidation using lipophilic antioxidants derived from natural antioxidant molecules was a logical choice to reduce deleterious oxidative stress. Four natural phenolic derivatives were selected in this study for their potent antioxidant properties or for their previous evaluation in RPE cell assays: phloroglucinol [15], resveratrol [14], catechin, and quercetin [46,47]. Among them, natural quercetin has been largely evaluated in the field of retina dystrophies for its direct or indirect antioxidant properties: Cao et al [18] demonstrated the ability of quercetin to protect human RPE cells from oxidative stress in vitro via suppression of pro-inflammatory cytokines and inhibition of apoptosis pathway.…”
Section: Discussionmentioning
confidence: 99%
“…One promising solution to low oral bioavailability is the development of nanodelivery systems able to maintain the structural integrity of the bioactive molecules (95).…”
Section: Other Considerations and Future Needsmentioning
confidence: 99%
“…Furthermore, research should shift the focus to studying antimicrobial properties of phenolics in vivo (92)(93)(94)(95)(96)(97)(98)(99)(100)(101). More animal and human experiments should be conducted in this field to establish general principles affecting their absorption in vivo.…”
Section: Other Considerations and Future Needsmentioning
confidence: 99%
“…Natural products and isolated natural compounds face several challenges and weaknesses that can compromise their therapeutic efficacy, including poor bioavailability and decreased water solubility, physical and chemical instabilities, rapid metabolism, and BBB crossing. These reviews of the literature provide more details [199][200][201]. However, numerous natural compounds, including resveratrol [202] and curcumin [203,204], have been reported to have low bioavailability and limited stability due to degradation or transformation into inactive derivatives [205,206].…”
Section: Limitations Future Prospects and Challengesmentioning
confidence: 99%